URGENSI PERUBAHAN PENGATURAN ORGANISASI ADVOKAT UNTUK MEWUJUDKAN FUNGSI HUKUM - Robert L Simanungkalit; Appe Hutauruk; Mardiman Sane; Sunarno (LPPM STIH Awang Long, 2026)
The enactment of the National Criminal Code under Law Number 1 of 2023 and the Criminal Procedure Code under Law Number 20 of 2025 marks a major reform of Indonesia's criminal justice system by reinforcing the position of advocates as equal law enforcement officers. Nevertheless, the effectiveness of these reforms is constrained by the fragmented structure of advocate organizations, which creates inconsistencies in professional standards, ethical enforcement, legal education, and institutional accountability. This study examines the urgency of reconstructing the regulation of advocate organizations to support the implementation of advocates' functions within the new criminal justice framework and proposes an institutional model that promotes professionalism, integrity, and legal certainty. The research applies a socio-legal approach with a dominant normative juridical method through library research, utilizing legislation, court decisions, books, and scientific journals as primary and secondary legal materials. The findings indicate that the current multi-bar system weakens professional standardization and ethical supervision, thereby reducing advocates' effectiveness in fulfilling their constitutional role. The study concludes that regulatory reconstruction is essential through an integrated institutional framework that standardizes professional education, strengthens ethical enforcement, and improves supervision while respecting the constitutional freedom of association. Such reform is expected to reinforce the advocate profession as an officium nobile and enhance justice, legal certainty, and the effectiveness of Indonesia's criminal justice system.